Cyonasua zettii sp. nov. (Procyonidae, Mammalia) from the Late Miocene of Central Argentina and a review of the fossil record of Cerro Azul Formation - Hontecillas Tamayo, Daniel; Soibelzon, Leopoldo Héctor; Montalvo, Claudia I.; Bonini, Ricardo Adolfo (Taylor & Francis, 2023)
A detailed taxonomic study of all known fossil specimens assigned to Procyonidae from sediments of Cerro Azul Formation (early Huayquerian Stage/Age, Late Miocene) outcroping at La Pampa and Buenos Aires provinces (Argentina) is presented here. Our study led us to propose a new species, Cyonasua zettii sp. nov. coming from La Pampa Province. In addition another six specimens studied, coming from La Pampa and Buenos Aires provinces, are assigned to Cyonasua longirostris and four specimens are assigned to Cyonasua sp. because its fragmentary nature prevents a determination at species level. The specimens described here are among the oldest records for the Order Carnivora (Mammalia) in South America.